"Ce Noir qui aurait pu être mon frère": Race and Fraternité in Marie NDiaye's Fiction. Issue 3 (27th May 2019) - Jensen, Laura
Abstract: Marie NDiaye's novels engage with race and identity in profound, if elusive, ways. In this article, I contend that NDiaye uses allegory to suggest what cannot be stated directly. In a Benjaminian fashion, she uses literary and artistic fragments to both draw connections and expose fissures between the Départements d'Outre-Mer (D.O.M.) and the metropole, between the era of the French slave trade and the present, and between black and white French citizens. I show that the politics of NDiaye's works come into sharper relief when considered within the particular political moment of their publication. On May 23, 1998, forty thousand people descended on the streets of Paris in the name of memory to demand that France recognize the slave trade as a crime against humanity. Their call was answered on May 10, 2001 when the "Loi Taubira" passed the Senate. 1 Between the march and the passing of the Loi Taubira, NDiaye published two works haunted by the slave trade: her 1999 novella, La Naufragée, and her 2001 novel, Rosie Carpe . La Naufragée and Rosie Carpe engage with the memory of the slave trade and the devoir de mémoire through an essential question of fraternité . They are books that ask, "Who counts as my brother, my equal, my fellow man?"